Performance analysis of a new mobility/QoS-aware architecture - Lopes, Nuno Vasco (2011)
Ideally, the future Internet must provide acceptable Quality of Service (QoS) to mobile users that are running real-time applications and are moving across different access points at high speeds. The user mobility presents a great challenge to the network layer in order to maintain users on going connections. Currently, the Internet protocol that manages the user mobility at the network level is the Mobile Internet Protocol (MIP). This protocol, when a mobile user changes its point of attachment, maintains the same IP address for mobile node, so that user mobility became invisible to the application level and thus avoiding a connection interruption. Although, MIP standard allows the user mobility while maintaining an uninterrupted connection to an application, it does not have any concerns with the QoS support provided to applications with more strict performance requirements such as real-time applications. This paper addresses the issue of mobility and QoS management principles as well as the mobility and QoS management integration in the sense of build a QoS-aware architecture for mobile Internet. After covering the mobility and QoS management principles and integration, this paper also proposes a new QoS-aware architecture for mobile Internet. This new architecture takes into account the specific characteristics of mobile networks in order to design an integrated Mobility/QoS-aware management architecture suitable for real-time applications requirements. The simulation results indicate that the suggested architecture is able to provide acceptable QoS levels to real-time applications that are running in mobiles devices.